The effect of pro-, pre- and synbiotics on the health of mink, morphometric parameters of their digestive tract, and microbiological analysis of its contents - Małgorzata Piórkowska (Polish Society of Animal Production, 2020)
The aim of the study was to analyse the effect of selected feed additives (pro-, pre- and synbiotics) on the health of mink, morphometric parameters of their digestive tract, and microbiological identification of its contents. The observations were made on pastel mink assigned to the following dietary treatments: group I – standard farm feed without supplements, group II – probiotic-supplemented feed, group III – prebiotic-supplemented feed, and group IV – synbiotic-supplemented feed. The feed additives were found to affect the growth and weight gains of the mink. Body weight at winter fur priming ranged from 1.45 to 2.54 kg in females and from 2.70 to 4.20 kg in males. During the rearing period (weaning to slaughter), the highest weight gains were observed in the group receiving prebiotics – on average 760 g in females and 1970 g in males. Analysis of the morphometric parameters of the digestive tract showed highly significant differences between means for the groups, except for the weight of the lungs and spleen and the length of the stomach. The mean concentration of total bacteria in the intestinal contents was similar in groups II and III (8.5-9.4 x 104 CFU/g), higher in group IV, and highest in the control group (5.9 x 106 CFU/g). Among the bacteria identified, Corynebacterium was dominant in all groups. The total fungal count in the intestinal contents was lowest in the mink receiving prebiotics. The dominant fungi were Candida, particularly Candida glabrata. The proportion of fungi of this genus varied between groups from 84.5% to 89.5%. The other fungi identified in the digesta were Rhizopus spp. and Aspergillus spp.